Restorative justice - Sliva, Shannon M. (Handbook of forensic social work, 2024)
Restorative justice is a community-based approach to harm response that is increasingly used in criminal legal settings as an alternative or supplement to court and correctional procedures. It is uniquely situated for social work practice due to its focus on human relationships. This chapter will offer an introduction to restorative justice and discuss the theoretical bases of this approach. It will then identify the restorative justice practices most commonly used in criminal legal settings and summarize empirical support for their efficacy with justice-involved populations. Finally, it will offer a case study depicting the use of a restorative justice approach to respond to community violence and highlight the challenges and opportunities for social workers in this unique practice arena.